Quercetin is a foe in the heart by targeting the hERG potassium channel - Zihao Lu; Shuwen Li; Rui Wei; Wenwen Li; Yuqian Huang; Tingting Yang; Meng Yan (Iranian Journal of Basic Medical Sciences, 2024)
Objective(s): Quercetin is a plant flavonoid known for its pharmacological activities, such as antioxidant, anti-inflammatory, and anti-cancer properties. However, there is limited information available regarding its potential toxicities. A previous study showed that quercetin can inhibit human ether-a-go-related gene (hERG, also named KCNH2) currents, which may lead to long QT syndrome, torsade de pointes (TdP), and even sudden cardiac death. This study aimed to investigate the effects of quercetin on hERG and its potential mechanism.Materials and Methods: hERG currents and action potential duration (APD) were assessed using the patch clamp technique. Molecular docking was employed to elucidate the binding sites between quercetin and hERG. Transfection of wild-type or mutant plasmids was used to verify the results of molecular docking. Western blot was performed to determine the expression levels of hERG, transcription factor SP1, molecular chaperones HSP70 and HSP90, phosphorylated E3 ubiquitin ligase p-Nedd4-2, serum- and glucocorticoid-inducible kinase (SGK1), and phosphatidylinositol 3-kinase (PI3K). Immunoprecipitation was conducted to evaluate hERG ubiquitination.Results: Quercetin acutely blocked hERG current by binding to F656 amino acid residue, subsequently accelerating channel inactivation. Long-term incubation of quercetin accelerates Nedd4-2-mediated ubiquitination degradation of hERG channels by inhibiting the PI3K/SGK1 signaling pathway. Moreover, the APD of human induced pluripotent stem cell-derived cardiomyocytes (hiPS-CMs) is significantly prolonged by 30 μM quercetin.Conclusion: Quercetin has a potential risk of proarrhythmia, which provided useful information for the usage and development of quercetin as a medication.